Conditions of emergence of OEM's reverse supply chains - Akram El Korchi; Dominique Millet (Journal of Remanufacturing, 2014)
Although academic research and some industrial experiences show that a reverse supply chain (RSC) based on remanufacturing offers the possibility to transform the constraint of environmental regulations on product recovery into an opportunity for value creation, few companies have managed to set up their own RSCs. Five research propositions on the condition of emergence of RSCs follow from a literature review and are applied to a case study from a global player in the electrical and electronic equipment (EEE) industry. The findings support the importance of an integrated approach for the design and implementation of a RSC. This integrated approach responds to the traditional questions of OEMs, 'Why' set up a RSC?; 'What' main conditions must be taken into account in the three segments of a RSC (procurement, production, and distribution)?; and 'How' can these conditions be satisfied?
Keywords: 650; Remanufacturing; Reverse supply chain; Conditions of emergence